2016
DOI: 10.1017/s1751731116000690
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-intake-level-dependent regulation of intestinal development in newborn intrauterine growth-restricted piglets via glucagon-like peptide-2

Abstract: The objective of the present study was to investigate the intestinal development of newborn intrauterine growth-restricted (IUGR) piglets subjected to normal nutrient intake (NNI) or restricted nutrient intake (RNI). Newborn normal birth weight (NBW) and IUGR piglets were allotted to NNI or RNI levels for 4 weeks from day 8 postnatal. IUGR piglets receiving NNI had similar growth performance compared with that of NBW piglets. Small intestine length and villous height were greater in IUGR piglets fed the NNI th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…From days 15 to 26, the BWs of animals treated with pGLP-2 microspheres were significantly higher than those of piglets in the control IUGR group. Importantly, the weaning weight in day 26 of piglets in the pGLP-2 group catched up to the BW of the normal birth weight group, as revealed by Liu et al [11].…”
Section: Administration Of Pglp-2 Microspheres Achieved Catch-up Growmentioning
confidence: 61%
See 3 more Smart Citations
“…From days 15 to 26, the BWs of animals treated with pGLP-2 microspheres were significantly higher than those of piglets in the control IUGR group. Importantly, the weaning weight in day 26 of piglets in the pGLP-2 group catched up to the BW of the normal birth weight group, as revealed by Liu et al [11].…”
Section: Administration Of Pglp-2 Microspheres Achieved Catch-up Growmentioning
confidence: 61%
“…week after birth. Liu et al [11] demonstrated significantly increased the villous height of IUGR piglets injected with GLP-2 compared with the control group under the condition of restricted nutrient intake.…”
Section: Pglp-2 Microspheres Improve the Pancreatic Secretion Functiomentioning
confidence: 98%
See 2 more Smart Citations
“…Chronically increased amino acids during the late phase of gestation improved insulin secretion of islet cell in growth-restricted fetal sheep 5 . When LBW piglets received a similar level of nutrition as piglets born with normal birth weight (NBW), they had equal growth performance compared with that of NBW piglets 6 . Low birth weight pigs provided with a high quality and expensive dietary regime might ensure maximum growth and increased profitability 7 .…”
Section: Introductionmentioning
confidence: 99%